Occupational asthma due to chamomile: case report - Cerri, Silvano; Bernabeo, Ferruccio; Valsecchi, Eleonora; Chiappino, Giovanni (La Medicina del Lavoro, 2017)
We report the case of a worker employed in the packaging of herb infusions who came to our attention because he was suffering from breathing disorders caused by occupational exposure to chamomile dusts. The diagnostic procedure we followed highlighted a baseline lung function within the normal range, while the skin prick tests and the RAST test were positive to both seasonal aeroallergens and chamomile. To perform a specific bronchial provocation test, the patient was challenged in an exposure chamber with nebulization of an extract from chamomile flowers. This procedure, that we had already applied for other occupational allergens, induced in the patient an immediate bronchospastic type reaction, documented by a 17% reduction of FEV1 from baseline. It also produced a significant increase in bronchial non specific hyperresponsiveness and a remarkable rise of nitric oxide, in comparison with the pre exposure observed values. We concluded for a diagnosis of occupational asthma caused by chamomile.